2018
DOI: 10.3400/avd.cr.17-00033
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Traumatic Retrograde Type A Aortic Dissection Accompanied by Multiorgan Injuries

Abstract: A 75-year-old woman was involved in a traffic accident and suffered retrograde type A aortic dissection, multiple rib fractures, and grade II hepatic injury accompanied by intraperitoneal bleeding. We performed total arch replacement using an open stent graft with cardiopulmonary bypass and circulatory arrest. This procedure requires anticoagulation and hypothermia, which are principally contraindicated in severe trauma patients. However, this situation was resolved by managing the patient non-operatively for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…A surgical approach requiring CPB can be applied only in limited cases because BAI is often associated with active bleeding from multiple injuries [2] . A previous case report demonstrated the clinical course of a patient with retrograde type A aortic dissection who underwent delayed total aortic arch replacement with CPB [4] . This report showed successful outcomes through delayed surgery after confirming that hemostasis had occurred at other injury sites.…”
Section: Discussionmentioning
confidence: 99%
“…A surgical approach requiring CPB can be applied only in limited cases because BAI is often associated with active bleeding from multiple injuries [2] . A previous case report demonstrated the clinical course of a patient with retrograde type A aortic dissection who underwent delayed total aortic arch replacement with CPB [4] . This report showed successful outcomes through delayed surgery after confirming that hemostasis had occurred at other injury sites.…”
Section: Discussionmentioning
confidence: 99%
“…However, the prognosis of TAI may be catastrophic. It is reported that more than 75% of TAI patients die before they are transferred to a medical center, and more than half of the remaining patients die within 24 hours [ 6 ]. The main causes of early death in patients with TAI include insufficient tissue perfusion and hemodynamic instability [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, ascending aorta is usually not involved without direct hit on the chest or rapid deceleration. 4,10 In addition, she never presented with any chest and back pain previously, and she had never been diagnosed with an aortic dissections. Therefore, we cannot confirm whether this was a newly developed dissection or a worsening intrinsic subclinical dissection.…”
Section: Discussionmentioning
confidence: 99%